The Effect of Excise Tariff and Compliance of Cigarettes Manufacturer to The Excise Revenue of Cigarettes in Indonesia - Andriyan Wahyu Wicaksono (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The objectives of this research is to analyze the effect Of Excise Tariff and Compliance Of Cigarettes Manufacturer to The Excise Revenue of Cigarettes. The test of hypothesis by using the partial regression analysis techniques (Partial Least Square/PLS) The research data is secondary data obtained from the Directorate General of Customs and Excise (DJBC) within a period of three years (2014-2016). The research sample consisted of 8 (eight) machine-made cigarettes (SKM) manufacturer of class I. The data was being established in the semester period starting from the second half of 2014, so it obtained 40 data observation. The result of research states that the excise tariff does not have the effect significantly to the The Excise Revenue of Cigarettes, while the compliance of Cigarettes Manufacturer has the effect positively and significantly to the excise revenue of cigarettes. The conclusion that can be taken from the results of this analysis is that the excise tariff for machine-made cigarettes manufacturer of class I does not have the effect significantly to the excise revenue of cigarettes, meanwhile the cigarettes manufacturer compliance has a significant effect on excise revenue. The recommendation for future policy are required to be prudent in applying the new tariffs and measurement of the profile score of manufacturer and importers of tobacco product must be improved.